Pengaruh Electronic Word of Mouth, Destination Image, Attitude Toward Destination dan Destination Trust terhadap Visit Intention: Studi pada Generasi Z di Jabodetabek - Aldrian; Usep Suhud; Ika Febrilia (Jurnal Bisnis, Manajemen, dan Keuangan, 2022)
This study aims to examine the effect of e-wom, destination image, attitude toward destination, destination trust, and visit intention. This research uses quantitative methods. Collecting data using a questionnaire. The subjects of this study were 217 respondents who live in the Jabodetabek area. Data analysis using SPSS and AMOS version 24. The results show that the first hypothesis proves that e-WoM has a positive and significant effect on the image of the destination received. The second hypothesis proves that e-WoM has a positive and significant effect on attitudes towards accepted goals. The third hypothesis proves that e-WoM has a positive and significant effect on the goals of trust received. The fourth hypothesis proves that e-WoM has a positive and significant effect on rejected visit intentions. The fifth hypothesis proves that the image of the destination has a positive and significant effect on the intention of being rejected. Hypothesis Prove that attitude towards the destination has a positive and significant effect on visit intention is rejected. The seventh hypothesis proves that destination trust has a positive and significant effect on the intention of the visit received. Penelitian ini bertujuan untuk menguji pengaruh e-wom, destination image, attitude toward destination, destination trust, dan visit intention. Penelitian ini menggunakan metode kuantitatif. Pengumpulan data menggunakan kuesioner. Subjek penelitian ini adalah 217 responden yang berdomisili di wilayah Jabodetabek. Analisis data menggunakan SPSS dan AMOS versi 24. Hasil penelitian menunjukkan bahwa hipotesis pertama membuktikan e-WoM berpengaruh positif dan signifikan terhadap destination image diterima. Hipotesis kedua membuktikan e-WoM berpengaruh positif dan signifikan terhadap attitude toward destination diterima. Hipotesis ketiga membuktikan e-WoM berpengaruh positif dan signifikan terhadap destination trust diterima. Hipotesis keempat membuktikan e-WoM berpengaruh positif dan signifikan terhadap visit intention ditolak. Hipotesis kelima membuktikan destination image berpengaruh positif dan signifikan terhadap visit intention ditolak. Hipotesis keenam membuktikan attitude toward destination berpengaruh positif dan signifikan terhadap visit intention ditolak. Hipotesis ketujuh membuktikan destination trust berpengaruh positif dan signifikan terhadap visit intention diterima.